Intersection between sleep and neurovascular coupling as the driving pathophysiology of Alzheimer's disease. (November 2020) - Kapadia, Anish; Mirrahimi, Arash; Dmytriw, Adam A.
Abstract: Alzheimer's disease (AD) is the commonest cause of dementia. There are tremendous personal and systemic costs associated with the disease. Although there has been significant progress in understanding the disease process, the precise pathophysiologic mechanism remains elusive. The amyloid hypothesis is the leading theory with impaired clearance of the amyloid beta (Aβ) believed to be the underpinning disease process. However, what triggers and propagates the accumulation of Aβ remains unclear. We propose that the impairment of neurovascular coupling triggers a cascade that ultimately leads to impaired Aβ clearance. With aging there is a generalized decline in cerebral blood flow and impairment of cerebrovascular reactivity. With impairment of this neurovascular coupling, the normal bulk clearance of cerebrospinal fluid and interstitial fluid (ISF) becomes hindered. We postulate that this clearance process occurs during non-rapid eye movement slow wave sleep, driven by the tight neurovascular coupling, via a pump-like action. The impairment of ISF clearance results in change in the interstitial microenvironment from accumulation of metabolites, reactive oxygen species, metal ions and results in decreased pH. The changes in the microenvironment promotes the accumulation and aggregation of Aβ, heralding the disease process.